Room temperature hydrogen sensing with polyaniline/SnO2/Pd nanocomposites - Pippara, Rohit Kumar; Chauhan, Pankaj Singh; Yadav, Anshul; Kishnani, Vinay; Gupta, Ankur (Micro and Nano Engineering, 2021)
In this work, we report unique hybrid composite film fabricated with the amalgamation of metal, semiconductor and polymers for hydrogen sensing application at room temperature. Fabrication of a novel nanocomposite film based on tin oxide (SnO2) nanosheets with polyaniline (PANI) doped with palladium (Pd) is performed using the hydrothermal synthesis technique. Functional aspects of the fabricated films are investigated with XRD, Raman spectra, FESEM, and FTIR spectral analysis. Interactions of the H2 gas molecules with SnO2, SnO2-Pd, PANI, PANI-SnO2, PANI-SnO2-Pd nanocomposite are also theoretically studied. Using first-principles density functional theory, the effects of gas adsorption on the electronic and transport properties of the sensor are examined. The computations show that the sensitivity of the SnO2 to the H2 gas molecules is considerably improved after hybridisation with Pd and, the sensitivity of the PANI to the H2gas molecules is considerably improved after hybridisation with SnO2.Gas sensing characteristics of fabricated films of SnO2, PANI and composite of SnO2/PANI/Pd are also experimentally investigated at room temperature with varying concentration level ranging from 50 to 400 ppm. The highest sensitivity among all the films at room temperature has been observed as ~540% for the SnO2/Pd film at 0.4% of the target gas and performance factor (the ratio of response percentage to total cycle time) is evaluated highest in Pd doped PANI-SnO2 film. Our results reveal the promising future of SnO2, PANI and Pd associated hybrid films in the development of ultra-high sensitive gas sensors. [Display omitted] •We report unique hybrid composite film fabricated with the novel nanocomposite film based on tin oxide (SnO2) nanosheets, polyaniline (PANI) doped with palladium (Pd) for room temperature hydrogen sensor.•Results obtained from the first-principles density functional theory show that the sensitivity of the SnO2 to the H2 gas molecules is considerably improved after hybridisation with Pd and the sensitivity of the PANI to the H2 gas molecules is considerably improved after hybridisation with SnO2.•The highest sensitivity among all the films at room temperature has been observed as ~540% for the SnO2/Pd film at 0.4% of the target gas and performance factor is evaluated as highest in Pd doped PANI-SnO2 film.